UNIT 9.2 Immunofluorescence Microscopy. Issue 10 (1st May 2015) - Asai, David J.
Abstract : The visualization of fluorescently tagged molecules is a powerful strategy that can contribute to the understanding of the complex dynamics of the cell. A particularly robust and broadly applicable method is immunofluorescence microscopy, in which a specific fluorescently labeled antibody binds the molecule of interest and then the location of the antibody is determined by fluorescence microscopy. The effective application of this technique includes several considerations, including the nature of the antigen, specificity of the antibody, permeabilization and fixation of the specimen, and fluorescence imaging of the cell. Although each protocol will require fine‐tuning depending on the cell type, the antibody, and the antigen, there are steps common to nearly all applications. This unit provides protocols for visualization of the cytoskeleton in two very different kinds of cells: flat, adherent fibroblasts and thick, free‐swimming Tetrahymena cells. © 2015 by John Wiley & Sons, Inc.